Enhancing STEM Awareness Through University Outreach Program in Rural School - Jusoh, Muhammad Noor Hazwan; Gani, Paran; Hadibarata, Tony; Jusoh, Muhammad Noor Hisyam (Acta Pedagogia Asiana, 2025)
Clean water awareness through STEM (Science, Technology, Engineering, and Mathematics) activities has become increasingly relevant, especially in rural areas where issues like water pollution and limited access to clean water persist. This paper described an outreach program with the aim of boosting both STEM understanding and health awareness among primary school students in a rural Malaysian community. The sessions were conducted hands-on, involving simple experiments and water filtration demonstrations using readily available materials. These activities highlighted experiential and inclusive learning, aligning with the goals outlined in the Malaysia Education Blueprint 2013–2025. During the program, students explored the science behind water contamination and its health impacts, followed by building their basic water filters. Students responded well during quizzes and interactive tasks, which helped track their learning progress. Notably, their awareness of waterborne diseases and confidence in applying basic filtration methods increased significantly from 15% before the program to full participation and understanding afterwards. Besides gaining knowledge, the activities seemed to shift their attitudes. Many students started asking questions about their household water sources, showing a level of curiosity that was not there before. This kind of learning rooted in real-life context demonstrated that STEM outreach does teach science as well as allows young learners to care about their environment and health. The model used in this program has strong potential to be adapted for other communities where resources may be limited but the need for awareness is in need.